2015
DOI: 10.1890/14-0698.1
|View full text |Cite
|
Sign up to set email alerts
|

What determines tree mortality in dry environments? a multi‐perspective approach

Abstract: Forest ecosystems function under increasing pressure due to global climate changes, while factors determining when and where mortality events will take place within the wider landscape are poorly understood. Observational studies are essential for documenting forest decline events, understanding their determinants, and developing sustainable management plans. A central obstacle towards achieving this goal is that mortality is often patchy across a range of spatial scales, and characterized by long-term tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 133 publications
2
26
3
Order By: Relevance
“…No indication of thinning stress was observed in our study. Our results disagree withDorman et al (2015b) who proposed for P. halepensis forests growing in a semiarid environment (annual rainfall & 300 mm) that thinning will not increase survival probability of the remaining trees when facing extreme drought.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…No indication of thinning stress was observed in our study. Our results disagree withDorman et al (2015b) who proposed for P. halepensis forests growing in a semiarid environment (annual rainfall & 300 mm) that thinning will not increase survival probability of the remaining trees when facing extreme drought.…”
contrasting
confidence: 99%
“…The consequences of prolonged drought were reflected in the studied forest through an exceptionally high rate of tree mortality (*20 %) observed in the non-thinned control plots during the study period. Extensive mortality in mature Pinus halepensis forests was reported recently throughout Israel and related to a series of consecutive drought years (Dorman et al 2013(Dorman et al , 2015b. Our results showed that thinning treatments alleviated drought stress, promoted tree growth, and reduced tree mortality with these outcomes being more pronounced with increasing thinning intensity.…”
Section: Discussionsupporting
confidence: 71%
“…However, there does not appear to be a consistent suite of factors that could reliably predict patterns of mortality. High mortality rates were positively related to age and negatively related to density in planted stands of Pinus halepensis Miller (Dorman et al 2015). This result does not support the commonly-held view that the probability of drought survival increases at lower stand densities, despite the assumption that levels of inter-and intra-specific competition and available resources are all improved with fewer trees in the stand.…”
Section: Introductioncontrasting
confidence: 61%
“…Demchik and Sharpe (2000) observed high species mortality in sample plots with low calcium-to-aluminum ratios in A and B soil horizons. Dorman et al(2015) found that rapid infiltration of water, particularly in sandy soils, can cause the water to pool at deeper levels, making the water inaccessible 2016, VOL. 92, N o 3 -THE FORESTRY CHRONICLE 337…”
Section: Introductionmentioning
confidence: 99%
“…Determinants of when and where mortality events will occur within a landscape, and how they will affect different species in the forest and its corresponding structure and function are poorly understood (Dorman et al. ).…”
Section: Introductionmentioning
confidence: 99%